A Field Guide to Grad School : Uncovering the Hidden Curriculum - Calarco, Jessica McCrory, 1983- (Book collections on Project MUSE., 2020)
"Some of the most important things you need to know to succeed in graduate school-like how to choose a good advisor, get funding for your work, and whether to celebrate or cry when a journal tells you to revise and resubmit an article-won't be covered in any class. They are part of a hidden curriculum that you are just expected to know or somehow learn on your own-or else. In this comprehensive survival guide for grad school, Jessica McCrory Calarco walks you through the secret knowledge and skills that are essential for navigating every critical stage of the postgraduate experience, from deciding whether to go to grad school in the first place to finishing your degree and landing a job. An invaluable resource for every prospective and current grad student in any discipline, A Field Guide to Grad School will save you grief-and help you thrive-in school and beyond"--